The association between endometriosis and risk of endometrial cancer and breast cancer: a meta-analysis - Ye, Jiatian; Peng, Hongling; Huang, Xia; Qi, Xiaorong (BMC women's health, 2022)
Endometriosis (EMS) is confirmed pathophysiologically to be an estrogen-dependent disease, similar to endometrial hyperplasia/cancer and breast cancer. Epidemiological and biological data on endometriosis might explain links between endometriosis and these cancers. We sought to identify the differences in the risk of endometrial cancer and breast cancer between women with and women without endometriosis. We searched PubMed, EMBASE, the Cochrane Library, and four Chinese databases (CNKI, VIP, WanFang, CBM) to identify relevant studies published online between January 2011 and March 2021. In our meta-analysis, we used the Newcastle-Ottawa Scale (NOS) to evaluate the design and quality of all studies, and we calculated the pooled risk ratio (RR) using the random model. The Q test and I were used to evaluate the degree of heterogeneity of eligible studies. We used funnel plots and Begg's and Egger's tests to assess publication bias. Of the 1369 articles, we finally included 14 cohort studies and seven case-control studies. Data from large cohort and case-control studies indicate that women with endometriosis had an increased risk of both endometrial cancer [RR, 1.662; 95% CI, (1.148-2.407)] and breast cancer [RR, 1.082; 95% CI, (1.001-1.169)]. Endometriosis can increase the risk of endometrial cancer and breast cancer, and women with endometriosis are recommended to receive routine screening in long-term management.